2006
DOI: 10.1007/s10811-006-9097-8
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Pattern of Reproduction Of Hizikia Fusiformis (Sargassaceae, Phaeophyta) from Nanao Island, Shantou, China

Abstract: The maturation pattern of sexual reproduction in Hizikia fusiformis (Harvey) Okamura (Sargassaceae, Phaeaophyta) was examined in 2003 at Yunao Bay, Nanao Island, Shantou, China. Maturation began in mid-April (seawater temperature 19-21 • C), reached the peak in mid-May (maturation rate ca. 70%, and seawater temperature 23.5-25 • C) and finished in lateJune (seawater temperature 27.5-30 • C). The Hizikia plants continued to gain the length from the beginning of maturation season to reach a maximum mean length o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 23 publications
2
18
1
Order By: Relevance
“…thunbergii thalli began to mature in early summer and receptacles appeared as day length increased. Our observations were consistent with work by Uchida (1993) and Zou et al (2006), who showed that long days initiated maturation of some Sargassum species. Although there is evidence that receptacles form under shorter photoperiod conditions in some Sargassum species (De Wreede, 1976;Yoshida et al, 2001), gametes are not released until the photoperiod increases (Yoshida et al, 1998).…”
Section: Discussionsupporting
confidence: 93%
“…thunbergii thalli began to mature in early summer and receptacles appeared as day length increased. Our observations were consistent with work by Uchida (1993) and Zou et al (2006), who showed that long days initiated maturation of some Sargassum species. Although there is evidence that receptacles form under shorter photoperiod conditions in some Sargassum species (De Wreede, 1976;Yoshida et al, 2001), gametes are not released until the photoperiod increases (Yoshida et al, 1998).…”
Section: Discussionsupporting
confidence: 93%
“…Size inequality would inevitably result in reproductive inequality of plants because size-dependent reproduction had been determined in many brown algae (Åberg 1996;Arenas and Fernández 1998;Zou et al 2006). The present observation that only 70% plants in natural population was fertile during the peak reproduction implied that the reproduction in S. thunbergii may be size-dependent (Fig.…”
Section: Discussionmentioning
confidence: 68%
“…An example of application of these results relates to the feasibility of growing seedlings in unshaded outdoor tanks. Direct solar irradiance on a sunny day at noon in May to June, when the reproduction event occurs, can reach 1800 μmol photons m −2 s −1 or higher (Zou et al 2006). Seedlings on collectors laid on the bottom in the outdoor tank with 50-cm water depth will certainly undergo photoinhibition (this investigation).…”
Section: Discussionmentioning
confidence: 93%